A new species of bezzia kieffer from Argentinean patagonia (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2013)
Bezzia, galesa Spinelli, a new Patagonian species, is described in all stages and illustrated by using binocular, phase-contrast and scanning electron microscopy. Immatures were collected associated to submerged filamentous algae in an unnamed pond in western Chubut province, Argentina, and reared to adults in the laboratory. Adults and immatures of this new species are compared with the most similar species Bezzia ventanensis Spinelli, Bezzia, roldani Spinelli et Wirth and Bezzia blantoni Spinelli et Wirth. Details on the rearing process and feeding behavior in laboratory are given.